A bionic noise reduction strategy on the trailing edge of NACA0018 based on the central composite design method. Issue 3 (June 2021) - Liu, Haoran; Lu, Yeming; Li, Yingyue; Wang, Xiaofang
New innovative approaches to reduce noise are of great significance in engineering. Taking the typical NACA0018 airfoil as the study target, the serrated treatment of the trailing edge is carried out with the bionic noise reduction technology. To boost the design efficiency and clarify the distributing laws between the design parameters and the noise performances, a special investigation about optimizing the NACA0018 airfoil's serrated trailing edge is implemented here. Firstly, a united parametric approach to represent various design schemes is proposed. Then, with the integration of the Computational Fluid Dynamics/Computational Acoustics analysis, Central Composite Design, and the Respond Surface Method, a bionic noise reduction strategy is established. The findings can be gotten as: taking into account the existence of the casing or wall near the span-end of the airfoil, the newly defined install location adjustment factor has an influence on the reduction noise, and the install location adjustment factor mainly affects the near-wall flow field of the serrated trailing edge; the optimal design scheme is obtained successfully, which can reduce the overall sound pressure level by about 2 dB in relative to the target; through the mechanism analysis of noise reduction, it can be found that the serrated trailing edge can suppress the development of the laminar separation bubbles, so the noise is reduced.